Comparison of the resonance behaviour of ottertail and voyageur style canoe paddles during the J-stroke - Runciman, R. J.; Lyle, K. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2013)
The canoe paddle has immense cultural and historical significance. Recognized throughout the world, the paddle has remained largely unchanged since its inception thousands of years ago. A major characteristic of performance in a recreational canoe paddle, and one that distinguishes a good paddle from a bad one, involves its tendency to resonate during use. With paddle resonance comes increased fluid resistance and a less efficient stroke. This study compared resonance tendencies of two major types of recreational canoe paddles, the ottertail and voyageur styles, in stiff and flexible formats. Data was acquired during open water canoe use and canoe velocities up to 2.0 m/s. During testing two 3-axis accelerometers were mounted on the shaft of the subject paddle. These accelerometers were then connected to onboard data collection instrumentation to record paddle resonance behaviour. Concurrent GPS-based canoe velocities were also recorded. The conventional J-stroke was used for all testing, and the canoe was repeatedly paddled between known points spaced approximately 100?m apart.Fluid driven resonance was observed at two specific phases of the J-stroke, the beginning of the control phase and the beginning of the recovery phase. The magnitude and characteristics of paddle resonance varied with the specific phase of the stroke, canoe paddle stiffness, style and velocity. The combination of these factors that resulted in the lowest paddle resonance of the combinations studied was a flexible ottertail style paddle, being paddled in the range of 1-1.8 m/s.